ANALISIS SEKTOR PERTAMBANGAN DAN PENGGALIAN MELALUI JALUR KREDIT DALAM MEKANISME TRANSMISI DI INDONESIA (TAHUN 2002-2012) - Regina Mayo (Universitas Katolik Widya Karya Malang, 2019)
This research analyzes the effectiveness of the credit channel in the monetary transmission mechanism in Indonesia with sectoral study. It is expected by using these credit channel, can indicate which sector contributes greatly to inflation and then handling the sector so there is not give a contribute significantly to inflation like the main purpose in the UU No. 3, 2004, 7 can be achieved, the stability of the rupiah, as reflectedin low inflation and stable.The VECM estimation technique with research periods 2002-2012 covering variables BI rate, credit rates of investment,credit rates of working capital, sectoral investment creditsectoral working capital credit, sectoral of GDP and inflation.The result shows: sectoral working capital credit of mining and quarrying which effectively explains inflation, it is because this sector is capital solid with advanced equipment and high technology, it takes a lot of fund. Kata Kunci: Monetary policy, credit channel, monetary ransmission mechanism